ASM Handbook. Volume 17, - Ahmad, Aquil; Bond, Leonard J. (ASM International, 2018)
Olume 17 describes the tools and techniques used in nondestructive evaluation and what they reveal about the integrity and operating potential of engineered materials and components. It covers the entire spectrum of sensing technologies from visible light inspection to ultrasonic, thermal, electromagnetic, and radiographic imaging. It explains how to identify and classify discontinuities in a variety of materials and how to determine if, when, and how they may lead to failure. The volume also contains case studies and examples showing how nondestructive methods are used to analyze castings and forgings, polymer and metal-matrix composites, powder metal and additively manufactured parts, solder joints, welded assemblies, and adhesive bonds. It also includes information on international standards and codes -- publisher.